Chitinozoans and scolecodonts from the Silurian and Devonian of Japan. (17th February 2019) - Vandenbroucke, Thijs R. A.; Hints, Olle; Williams, Mark; Wallis, Simon; Velleman, Jules; Kurihara, Toshiyuki; Tanaka, Gengo; Komatsu, Toshifumi; Männik, Peep; Siveter, David J.; de Backer, Tim
Abstract: Silurian and Devonian chitinozoans and scolecodonts are recorded from strata of the Hida‐Gaien Terrane, central Honshu. Silurian chitinozoans include Eisenackitina, Bursachitina, and the species Angochitina elongata . The latter provides a precise biostratigraphical tie between the Japanese succession and the Type Ludlow Series of the Welsh Borderland, UK, and indicates a Ludlow age (Gorstian or early Ludfordian) for the upper member of the Yoshiki Formation in the Ichinotani Valley. Chitinozoans from other Yoshiki Formation localities contain other specimens of Lagenochitinidae. Scolecodonts are more common than chitinozoans in the palynological residues, but are mostly represented by fragments or minor apparatus elements with a low biostratigraphical value. However, material from the Yoshiki and Fukuji Formations includes several species of Mochtyella as well as representatives of Oenonites, Kettnerites, Lunoprionella, Vistulella ? and possibly other placognath taxa. Scolecodonts are also present in the Silurian Middle Member of the Gionyama Formation, Kyushu, including a well‐preserved jaw of Pistoprion, and fragments of putative Kettnerites and Oenonites . These finds of scolecodonts suggest close similarity in assemblages between Paleozoic polychaete faunas of Japanese terranes and those of Baltica‐Laurentia. Abstract : We report on the first Silurian and Devonian palynomorphs (chitinozoans & scolecodonts) from strata of the Hida‐Gaien Terrane, central Honshu. The recovered chitinozoans allow us to correlate precisely between the Japanese succession of the Hida‐Gaien Terrane, central Honshu and the Type Ludlow Series of the Welsh Borderland, UK. Samples from the Silurian Middle Member of the Gionyama Formation in Kyushu yielded additional scolecodonts.